Prediction of future potential distributions of Pinus yunnanensis varieties under climate change - Feng, Jian; Wang, Bilei; Xian, Mingrui; Zhou, Shixing; Huang, Congde; Cui, Xinglei (Frontiers in Forests and Global Change, 2023)
Franch. (Pinaceae) is an important endemic tree species that serves as a critical constituent of the forest ecosystems and plays a significant role in forestry economic production in southwest China. P. yunnanensis comprises three varieties: var. yunnanensis, var. pygmaea and var.tenuifolia, with significant variation in traits, such as height and leaf size. This study aims to characterize the habitat conditions of the three varieties and predict their potential future distributions by employing MaxEnt model. Temperature seasonality (BIO4) emerged as the most influential factor affecting the distribution of var. yunnanensis; isothermally (BIO3) stands out as the most critical factor for the distribution of var. pygmaea; whereas mean annual fire occurrence (MAF) had the greatest impact on the distribution of var. tenuifolia. Under future climate conditions, the highly and moderately suitable habitats for all the three varieties are projected to decrease, while the lowly suitable habitats are projected to increase.The distribution centroids of all the three varieties are anticipated to shift to higher latitudes. Our study characterized the habitat conditions and predicted the potential future distribution of the three P. yunnanensis varieties, which could help the conservation and utilization of P. yunnanensis varieties.